2016
DOI: 10.1158/2326-6066.imm2016-a102
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A102: The fat in ovarian cancer: Immune-dependent tumor-promoting effects

Abstract: Because of the particular anatomy of ovaries, which are in close contact with the adipocyte-rich omentum, ovarian cancer frequently presents itself with established metastasis-like disseminated tumor islets along the omentum. The tropism of ovarian cancer cells for fat is well described. Indeed, adipocyte-derived free fatty acids have been causatively linked to cancer cell proliferation and invasive properties. Obesity is additionally linked to increased risk of ovarian cancer onset and, in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous investigations have shown that elevated inflammation markers, a sign of negative outcome in oncologic patients, are associated with decreased muscle mass but have no association with BMI [ 51 ]. Other studies investigating adipocyte-derived free fatty acids have shown a causative link to cancer cell proliferation and invasive properties, which might impact prognosis [ 52 ]. Such studies might lead to clinical recommendations, for example the earlier use of parenteral food to increase caloric intake and prevent the metabolomics switch.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that elevated inflammation markers, a sign of negative outcome in oncologic patients, are associated with decreased muscle mass but have no association with BMI [ 51 ]. Other studies investigating adipocyte-derived free fatty acids have shown a causative link to cancer cell proliferation and invasive properties, which might impact prognosis [ 52 ]. Such studies might lead to clinical recommendations, for example the earlier use of parenteral food to increase caloric intake and prevent the metabolomics switch.…”
Section: Discussionmentioning
confidence: 99%
“…Myocellular lipid accumulation promotes the secretion of several mediators (eg, inflammatory kinases and reactive oxygen species) or free fatty acids, which cause insulin resistance, activate cancer cell proliferation and invasiveness and impact prognosis. 48,49 Either intra-or extramyocellular adipose can change the shapes of muscle fibers, slow nutritive blood flowing to myocyte and impair the strength and velocity of muscle contraction, 48 which would eventually provide a broad area for tumors to spread, increase surgical blood loss and extend operation time. 50 Evidence inferred that cancer patients with myosteatosis are unlikely to achieve complete resection, 30 and consequently postoperative residuals will lead to a cancer relapse and treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…So far, metabolic disturbance and mechanical dysfunction of skeletal muscle have been recognized as the causes of the detrimental impacts of myosteatosis on survival. Myocellular lipid accumulation promotes the secretion of several mediators (eg, inflammatory kinases and reactive oxygen species) or free fatty acids, which cause insulin resistance, activate cancer cell proliferation and invasiveness and impact prognosis 48,49 . Either intra‐ or extramyocellular adipose can change the shapes of muscle fibers, slow nutritive blood flowing to myocyte and impair the strength and velocity of muscle contraction, 48 which would eventually provide a broad area for tumors to spread, increase surgical blood loss and extend operation time 50 .…”
Section: Discussionmentioning
confidence: 99%